Cellulase Enzyme Activity of Aspergillus fumigatus from Mangrove Soil on Lignocellulosic Substrate - K.M. Khaleel, V.V. Gilna and (Recent Research in Science and Technology, 2011)
Sawdust was used as lignocellulosic substrates for the production of cellulase enzyme using Aspergillus fumigatusÃ‚Â which was isolated from mangrove soil after pretreatment with 4% sodium hydroxide. Parameters like pH, temperature, nitrogen sources and inducers were optimized for the cellulase production.